Penerapan Metode Life-CycleCost dalam Perhitungan Evaluasi Ekonomi Jembatan untuk Penetuan Prioritas Penanganan Jembatan - Risang Aji Dananjoyo; Akhmad Aminullah; Arief Setiawan Budi Nugroho (Jurnal Teknosains, 2020)
Bridge oftentimes become a critical components of roads because it used to determine the maximum load capacity of a passing vehicle on the roads. The bridges require maintenance activity in the shape of general maintenance or periodically replacement while this is estimated in order that the bridge may continue to function properly. The economic evaluation of the Interurban Bridge Management System (IBMS) aims to determine the priority of bridge handling. One of the calculations required in NPV and IRR calculations used in priority handling is the cost of replacing the bridge. Over time, the Interurban Bridge Management System (IBMS) system must be constantly updated to continue to use in accordance with current circumstances and use new, better methods. This study uses Life-Cycle Cost (LCC) method as an alternative method to calculate the replacement cost of 5 bridges in Daerah Istimewa Yogyakarta in 2012. The IBMS method produces a priority sequence of bridge handling with Bogo bridge, Suru bridge, Winongo bridge, Kalasan B bridge and Duren bridge in sequence. The Life-Cycke Cost (LCC) method produces a priority sequence of bridge handling with Bogo bridge, Winongo bridge, Suru bridge, Kalasan B bridge and Duren bridge. The average initial cost of bridge replacement using both methods is 23.012%. The value earned using the Life-Cycle Cost method is always greater due to the addition of inspection fees, maintenance costs, and damage costs of the bridge.